2018
DOI: 10.1111/1365-2478.12677
|View full text |Cite
|
Sign up to set email alerts
|

A triple porosity scheme for fluid/solid substitution: theory and experiment

Abstract: Quantifying the effects of pore‐filling materials on elastic properties of porous rocks is of considerable interest in geophysical practice. For rocks saturated with fluids, the Gassmann equation is proved effective in estimating the exact change in seismic velocity or rock moduli upon the changes in properties of pore infill. For solid substance or viscoelastic materials, however, the Gassmann theory is not applicable as the rigidity of the pore fill (either elastic or viscoelastic) prevents pressure communic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 30 publications
(77 reference statements)
2
14
0
1
Order By: Relevance
“…Finally, let us note, that the results of this study are at variance with ultrasonic data on the same rock (Sun, Gurevich, Lebedev, Glubokovskikh, Mikhaltsevitch, et al, ; Sun, Gurevich, Lebedev, Glubokovskikh, Squelch, et al, ). In particular, Sun, Gurevich, Lebedev, Glubokovskikh, Mikhaltsevitch, et al () found that the Ciz‐Shapiro model underestimated both bulk and shear moduli of the rock saturated with octadecane and explained this discrepancy by the effect of stiffening of compliant pores (grain‐to‐grain contacts).…”
Section: Resultssupporting
confidence: 46%
See 2 more Smart Citations
“…Finally, let us note, that the results of this study are at variance with ultrasonic data on the same rock (Sun, Gurevich, Lebedev, Glubokovskikh, Mikhaltsevitch, et al, ; Sun, Gurevich, Lebedev, Glubokovskikh, Squelch, et al, ). In particular, Sun, Gurevich, Lebedev, Glubokovskikh, Mikhaltsevitch, et al () found that the Ciz‐Shapiro model underestimated both bulk and shear moduli of the rock saturated with octadecane and explained this discrepancy by the effect of stiffening of compliant pores (grain‐to‐grain contacts).…”
Section: Resultssupporting
confidence: 46%
“…Finally, let us note, that the results of this study are at variance with ultrasonic data on the same rock (Sun, Gurevich, Lebedev, Glubokovskikh, Mikhaltsevitch, et al, 2018;Sun, Gurevich, Lebedev, Glubokovskikh, Squelch, et al, 2018). In particular, Sun, Gurevich, Lebedev, Glubokovskikh, Mikhaltsevitch, et al (2018) found that the Ciz-Shapiro model underestimated both bulk and shear moduli of the rock saturated with octadecane and explained this discrepancy by the effect of stiffening of compliant pores (grain-to-grain contacts). In contrast, the low-frequency measurements for both bulk and shear moduli in the present study are consistent with the Ciz-Shapiro model, which suggests that the effect of stiffening of the compliant pores in presence of solid is negligible.…”
Section: Journal Of Geophysical Research: Solid Earthsupporting
confidence: 52%
See 1 more Smart Citation
“…However, the Gassmann theory has an important restriction: it assumes that the pressure in the pore fill is spatially uniform. Thus for rocks filled with solid substances or high-viscosity or non-Newtonian fluids, the Gassmann theory is invalid as the shear compliance of the pore fill impedes the pressure communication between different pores (Makarynska et al 2010;Saxena & Mavko 2014;Glubokovskikh et al 2016;Sun et al 2018). Ciz & Shapiro (2007, referred to as C&S model) derived an approximate extension of the Gassmann equation to a solid pore fill.…”
mentioning
confidence: 99%
“…Ciz & Shapiro (2007, referred to as C&S model) derived an approximate extension of the Gassmann equation to a solid pore fill. However, recent studies (Saxena & Mavko 2014;Glubokovskikh et al 2016;Sun et al 2018) show that the C&S model gives a lower bound to the elastic moduli of porous and fractured rocks saturated with a solid or high-viscosity liquid because it also assumes that stress throughout the pore fill is spatially uniform. This assumption should be accurate if all pores are of approximately the same shape, but can be violated if the pore space contains pores with a range of shapes and compliances.…”
mentioning
confidence: 99%